Sexual violence in Indonesian University: On students’ critical consciousness and agency - Fitri, Ainal; Haekal, Muhammad; Almukarramah, Almukarramah; Sari, Fitri Meliya (Universitas Islam Negeri Ar-Raniry, 2021)
This qualitative study analysed how aspects of critical consciousness in students played a role in the issue of sexual violence in a higher education institution. This research involved students, lecturers, and elements of higher education leaders of a university in Aceh, Indonesia. For the data collection method, the researchers used semi-structured interviews. The data was analysed using thematic analysis with the utilization of critical consciousness and student agency concept as the theoretical frameworks. This study found that aspects of critical consciousness played a significant role in dealing with sexual violence issues in university. Without critical consciousness, students would potentially err in analysing the issue of sexual violence. Aspects of students' critical consciousness were also influenced by the structure or discourse of higher education in viewing sexual violence. The tendency of campus to be more concerned with its good reputation also exacerbated the handling and prevention of sexual violence cases. The implication of this research is the finding that critical consciousness and institutional structure influence each other, both positively and negatively. To deal with sexual violence, a university must promote critical consciousness among students and academics, create pro survivors’ discourse and underpin students' agency, and most importantly, strive to cultivate gender equity perspective among university leaders. Future research should focus on investigating effective pedagogy to nurture critical consciousness for supporting the anti-sexual violence agenda in a higher education institution